DNA and Histone Methylation as Cancer Targets - Kaneda, Atsushi; Tsukada, Yu-ichi.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Humana Press, 2017)
This book will focus on DNA and histone methylation in epigenetics and describe how it is involved in the molecular mechanisms responsible for the development of cancer. Chapters will summarize the current knowledge of the molecular basis of DNA and histone methylation and explain how it is involved in cancer, describe the features of DNA and histone methylation associated with particular types of cancer, diagnostic/therapeutic applications, and future directions of DNA and histone methylation as cancer targets.
DNA and histone methylation in epigenetics -- The molecular basis of DNA methylation -- The molecular basis of DNA demethylation -- DNA methylation changes in cancer -- Misregulation of DNA methylation regulators in cancer -- The molecular basis of histone methylation -- The molecular basis of histone demethylation -- Misregulation of histone methylation regulators in cancer -- Other histone modifications -- DNA methylation and dysregulation of miRNA in cancer -- Genomic imprinting syndromes and cancer -- DNA and Histone Methylation in Brain Cancer -- DNA and Histone Methylation in Gastric Cancer -- DNA and Histone Methylation in Hematopoietic malignancy -- DNA and Histone methylation in Lung cancer -- DNA and Histone Methylation in Liver Cancer -- DNA and Histone Methylation in Colon Cancer -- DNA and histone methylation in prostate cancer -- DNA and histone modifications in cancer diagnosis -- DNA and histone modifications in cancer therapy -- Future perspective of DNA and histone methylation as cancer targets.
Keywords: Medicine; Cancer research; Biomedicine; Cancer research